The value of collaborative rounds for teacher professional learning in Australia - Mansfield, Caroline; Thompson, Greg (Professional Development in Education, 2017)
Teacher professional learning (PL) is viewed by governments, bureaucracies and school systems as important for improving teaching quality and effectiveness. This new enthusiasm, however, is set against a history of professional development in schools of marginal benefit. In response to this history, education authorities are interested in PL that emphasises collaborative, relevant and authentic opportunities for teachers. This article reports a study investigating the potential of a collaborative rounds-based approach for teacher PL conducted across three small primary schools in Western Australia. Using qualitative data gathered over a year, strengths and challenges of the rounds approach are explored. Findings show how this PL supported teacher learning, the perceived influence on classroom instruction and the benefits in working collaboratively. Challenges included time and logistics, overcoming anxiety about being observed and the process of learning observational skills. Implications for future implementation as well as policy and practice are discussed.
Keywords: Instructional Rounds; teacher collaboration; teacher observation; teacher professional learning